Ethnomathematics on the Gringsing batik motifs in Javanese culture - Permita, Adinda Indah; Nguyen, Tien-Trung; Prahmana, Rully Charitas Indra (Journal of Honai Math, 2022)
Mathematics cannot be separated from human life. However, mathematics is often taught directly through formulas and abstract mathematical forms at school and is less associated with students' daily lives. Hence, it makes it difficult for students to understand mathematics and often find it difficult to understand how mathematics can be useful in dealing with various problems in real life. Therefore, school mathematics needs to be reconnected with the reality of human life so that students can easily understand mathematics and use it to solve various daily life problems. This study explores ethnomathematics in Javanese culture, especially in the Gringsing batik motif. The ethnographic method was employed in this study, and the data was collected through literature review, observation, and interviews. The data was then analyzed before and according to the conditions in the field. The results showed that the Gringsing batik motif contains philosophical meanings, cultural values, and mathematical elements of plane shapes and geometric transformations. This research contributes to the context of learning mathematics. In addition, it also increases the knowledge of mathematics and culture and can be used as a reference in learning or similar research.